A new species of Senna (Leguminosae) from the Isthmus of Tehuantepec, Oaxaca, Mexico - Torres-Colín, Rafael; Saynes-Vásquez, Alfredo (Phytotaxa, 2019)
A new species of Senna from Mexico is described and illustrated. Morphologically it is similar to S. velutina from Brazil, but it differs in the type of indumentum from various parts of the plant; in the form of the stipules, leaflets, and pedicel gland; in the size and shape of the flower buds; in the shape of the sepals; in the width of the filaments of the abaxial stamens; and in the length of the central anthers, legume, and seeds. This species is endemic to the Juchitan District, in the Isthmus of Tehuantepec.